Pengaruh Limbah Bata Ringan dan Fly Ash Sebagai Filler terhadap Karakteristik Uji Marshal Asphalt AC-WC - Hairul Izwan; Anwar Efendy; Aulia Muttaqin; Hafiz Hamdani (Jurnal Talenta Sipil, 2026)
The need for road infrastructure development in Indonesia continues to increase, so a more optimal, sustainable and environmentally friendly asphalt mixture is needed. In the AC-WC wear layer which functions to receive traffic loads directly, the type of filler plays an important role in determining the stability, durability and long-term performance of the pavement. The limited availability of conventional fillers such as Portland cement and stone ash encourages the use of industrial waste materials as alternatives, including fly ash and light brick waste which have mineral characteristics and grain sizes that are suitable for fillers. This research aims to analyze the effect of variations in the composition of lightweight brick filler and fly ash on the Marshall parameters of AC-WC mixtures, including stability, flow and volumetric characteristics such as VIM, VMA and VFA. Tests were carried out experimentally in the laboratory using the Marshall method based on SNI, with three variations in filler ratios of 0.25%–0.75%, 0.50%–0.50%, and 0.75%–0.25% at an optimum asphalt content of 6%, as well as a total of 24 test objects. The results show that all formulations meet the 2018 Bina Marga standards, with VIM values of 4.46%, 4.52% and 4.73% respectively. VMA is 18.08%, 18.32% and 18.65%. As well as VFA 75.36%, 75.3% and 74.62%. The stability obtained respectively was 1311 kg, 1296 kg, and 1278 kg, while the flow values were 3.4 mm, 3.23 mm, and 3.38 mm. The combination of 0.25% lightweight brick and 0.75% fly ash provides the highest stability value. Overall, the use of light brick waste and fly ash is able to improve the performance of Marshall characteristics, meet technical requirements, and has great potential as a more economical and environmentally friendly alternative filler in AC-WC mixtures.